The Role of Media and Public Sphere in Development Issues: A Case Study of Daily Sakal - Salunkhe, Sumedha (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Media plays an important role in the development of society. By providing a platform for the dissemination of information, media can shape public opinion and influence the way people perceive and understand the world around them. For the development of society, keeping in mind the important issues, the media does the work of creating awareness among people. The present research focuses on the role of the media in developing issues. Sakal is a well-known media in Maharashtra. Sakal addresses developmental issues. Kolhapur is situated on the bank of the river Panchaganga. Panchganga is a famous water-body in the Indian city of Kolhapur in Maharashtra. It is a major river and tributary of the Krishna River that flows through the borders of Kolhapur and is formed by the other four rivers. These rivers are known as the Kasari, Kumbhi, Tulasi, and Bhogawati. Kolhapur’s Panchgaga River is the lifeblood of the Kolhapur district and the surrounding area facing the problem of pollution. Taking into consideration the seriousness of pollution, Sakal pointed towards how a public sphere would ideally solve the issue and help society. The present research focuses on the media’s role in triggering the issue of Panchganga pollution. Habermas’s concept of the public sphere also applies to this concept. The public sphere is an area of social life where public opinion can emerge. A case study method was adopted in this research. The data were collected from the Sakal Kollhapur edition.